2016
DOI: 10.1149/2.1151606jes
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy of Mackinawite FeS in Anodic Iron Sulfide Corrosion Products

Abstract: Raman spectroscopy in a confocal microscope was used to study electrochemically synthesized corrosion products from sour gas experiments. When exposed to oxygen-containing atmosphere, the initial mackinawite FeS corrosion product transformed under laser irradiation to hematite, Fe 2 O 3 . Measurements with a thin water layer on top of the corrosion products prevented the transformation, as drying was prevented. In situ Raman measurements of mackinawite formation avoided the problem of transformation completely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(51 citation statements)
references
References 79 publications
(169 reference statements)
4
46
1
Order By: Relevance
“…This is different from previous observations, where nanocrystalline mackinawite was already identified as the initial corrosion product after much shorter exposure times than the shortest used here . Overall, an initial, possibly nanocrystalline mackinawite then typically recrystallises to form crystalline mackinawite . A thermodynamic analysis of the system showed that pyrite is the expected, thermodynamically stable corrosion product in certain ranges of the predominance diagram , in general at higher electrode potentials and lower pH compared to mackinawite.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This is different from previous observations, where nanocrystalline mackinawite was already identified as the initial corrosion product after much shorter exposure times than the shortest used here . Overall, an initial, possibly nanocrystalline mackinawite then typically recrystallises to form crystalline mackinawite . A thermodynamic analysis of the system showed that pyrite is the expected, thermodynamically stable corrosion product in certain ranges of the predominance diagram , in general at higher electrode potentials and lower pH compared to mackinawite.…”
Section: Discussioncontrasting
confidence: 99%
“…Two sharp Raman bands were detected in the measurements at 209 and 290 cm −1 (shoulder). The bands are similar in position to those observed on bare iron and discussed in detail elsewhere . These bands are seen as an indication of microcrystalline mackinawite .…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…It has been found that the spectra of the dark inner portions, as shown in Figure , might consist of lepidocrocite, goethite, magnetite, maghemite and organic compounds. With regard to magnetite, it is essentially characterized by band around 670 cm −1 . Moreover, the Raman peaks found at 359 and 505 cm −1 can be attributed to maghemite .…”
Section: Resultsmentioning
confidence: 97%